(untitled) (Human Factors in Design, 2022)
This study proposes a set of usability recommendations for mobile learning systems. A Systematic Literature Review supported usability heuristics research focused on the mobile learning field. The applicability of these guidelines was observed through the interfaces of an educational app called “Encceja”. The work results bring a set of ten new usability recommendations that simultaneously integrate design aspects, navigability, and didactic approaches. It stands out as a differential of this set its completeness and adaptability of use, being able to be applied in smartphones, tablets and also appropriate for any educational context.